NOTES ON TAXONOMY OF ATHYRIUM NIGRIPES (BLUME) T. MOORE COMPLEX, AN INSIGHT FROM MOUNTAINS IN JAVA - Wita Wardani; Bayu Adjie; Kusumadewi Sri Yulita; Andi Salamah (Floribunda, 2023)
Athyrium nigripes is a highly variable species described and recorded mostly from Java and few from surrounding islands. There are different arguments on its delimitation and hence its extent of distribution. We attempted to elucidate disagreement on delimitation of four related species described from Java: Athyrium nigripes, Aspidium costale, At. pulcherrimum and At. nitidulum with phenetic approach. The analysis formed four clusters; cluster I consist of the large sized and include type specimen of At. pulcherrimum and Asp. costale, cluster II for plants with standard form and include type specimen of At. nigripes, cluster III only for serrated plants and cluster IV contain the At. nitidulum form. Since Asp. costale clustered in group I, this species is more closely related to At. pulcherrimum than to At. nigripes nested in group II.  Large size and degree of division indicate major clustering within the complex species.